Edukasi Pengawasan Orangtua terhadap Akses Novel Digital Bermuatan Pornografi pada Anak di Bawah Umur: Parental Supervision Education on Gadget Use by Minors as Readers of Digital Novels - Tsary, Syifa Rana; Saputra, Rian; Muttaqin, Ahmad Dicky (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service activity aims to provide parents with an understanding of the importance of providing underage children with access to digital novels to prevent them from falling prey to pornographic works. The target audience was the PKK mothers' association in Pucangsawit Village, Jebres District, Surakarta City. To achieve the stated objectives, the method used was normative, involving the review of various laws and regulations, combined with empirical studies that collected field data. This service was delivered as legal counseling to the community through lecture methods, module presentations, and digital novel displays. The results obtained from this Community Service agenda were increased knowledge of the participants regarding the dangers of the influence of digital novels containing pornographic elements if underage children consume this type of reading material.